Integration and Optimization of Heterogeneous Energy Resource Accounting Systems in Multi-Storey Buildings: Benefits and Challenges - Kelas'ev A. A. (A breakthrough in science: development strategies, 2024)
The article discusses the main aspects of integrating and optimizing heterogeneous energy resource accounting systems in multi-storey buildings. It describes benefits such as improved data accuracy and reduced operational costs, as well as challenges related to technical complexity and the need for standardization. Special attention is given to the analysis of methods for integrating various types of measuring instruments and software, which improves energy consumption management and ensures reliable data collection. Examples of successful implementations in various residential complexes are provided, illustrating real-world results and the economic efficiency of such approaches. The main technical and organizational challenges, including compatibility issues, data security problems, and the need to adapt existing systems, are also discussed. Recommendations for further development in this area are proposed, aimed at overcoming existing barriers and enhancing the interaction between different components of the energy resource accounting system.
Keywords: интеграция; оптимизация; integration; optimization; учет энергоресурсов; challenges; вызовы; energy resource accounting; heterogeneous systems; multi-storey buildings; гетерогенные системы; многоэтажные дома